2020
DOI: 10.5397/cise.2020.00318
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and treatment of calcific tendinitis of the shoulder

Abstract: Calcific tendinitis is the leading cause of shoulder pain. Among patients with calcific tendinitis, 2.7%–20% are asymptomatic, and 35%–45% of patients whose calcific deposits are inadvertently discovered develop shoulder pain. If symptoms are present, complications such as decreased range of motion of the shoulder joint should be minimized while managing pain. Patients with acute calcific tendinitis respond well to conservative treatment and rarely require surgery. In contrast, patients with chronic calcific t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
27
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 19 publications
1
27
0
4
Order By: Relevance
“…In our study, the mean size of the calcific deposit decreased significantly after US-GND, and 67.3% of patients had PVAS score ≤2, 59.3% had ASES score≥80, and 73.5% were satisfied to very satisfied. Thus, the success rate of US-GND in our study is comparable to that of previous studies, which was approximately 70% [ 6 , 8 , 10 , 11 ]. Repeated US-GND was performed in 14.3% patients in our study, which was slightly lower than that reported in previous studies (18%–45%) [ 10 , 23 ].…”
Section: Discussionsupporting
confidence: 89%
“…In our study, the mean size of the calcific deposit decreased significantly after US-GND, and 67.3% of patients had PVAS score ≤2, 59.3% had ASES score≥80, and 73.5% were satisfied to very satisfied. Thus, the success rate of US-GND in our study is comparable to that of previous studies, which was approximately 70% [ 6 , 8 , 10 , 11 ]. Repeated US-GND was performed in 14.3% patients in our study, which was slightly lower than that reported in previous studies (18%–45%) [ 10 , 23 ].…”
Section: Discussionsupporting
confidence: 89%
“…In our case, the injection technique was found to be correct, so other causes were considered, and following ultrasonography we found a linear calcification near the footprint of the subscapularis tendon, which immediately led to the probable diagnosis of the COVID-19 vaccination had precipitating the patient's formerly asymptomatic calcific tendinitis to symptomatic calcific tendinitis. The main symptom of this patient was also compatible with the diagnosis of calcific tendinitis because the symptoms were a sudden pain and limited range of motion of left shoulder after a COVID-19 vaccine injection [ 16 ]. This case is quite similar to an earlier case report of combined subacromial-subdeltoid bursitis and supraspinatus tear after a COVID-19 vaccination, which was determined to have precipitated an existing but asymptomatic rotator cuff tear to a symptomatic rotator cuff tear [ 17 ].…”
Section: Discussionmentioning
confidence: 95%
“…Calcific tendinitis can be diagnosed by patient history, physical examination, and/or imaging studies. Not all patients with calcific tendinitis have the clinical symptom of shoulder pain, and incidences of asymptomatic calcific tendinitis have been reported from 2.7% to 20% [ 16 ]. In our case, the injection technique was found to be correct, so other causes were considered, and following ultrasonography we found a linear calcification near the footprint of the subscapularis tendon, which immediately led to the probable diagnosis of the COVID-19 vaccination had precipitating the patient's formerly asymptomatic calcific tendinitis to symptomatic calcific tendinitis.…”
Section: Discussionmentioning
confidence: 99%
“…However, rotator cuff repair using side-to-side repair and suture anchors can facilitate rehabilitation with satisfactory clinical outcomes. 19 …”
Section: Discussionmentioning
confidence: 99%